ARCHITECTURAL MONUMENTS OF KARAKALPAKSTAN AND PROSPECTS FOR ENSURING THEIR ENVIRONMENTAL ACCESSIBILITY - Yusupbaevna, Kamalova Dilnoza (Research Focus International Scientific Journal, 2026)
Karakalpakstan is rich in minerals, with huge deposits of gas, iron, kaolin clays, Glauber salts, marble, and granite. The state economy is based on agriculture, including cotton growing, rice growing, the production of melons, vegetables, and licorice, as well as industrial Karakul breeding and industries represented by energy, metalworking, food, and textile production.